Selfless Love and Human Flourishing in Paul Tillich and Iris Murdoch, by Julia T. Meszaros - Fekete, David J (Religious Studies and Theology, 2017)
Selfless Love and Human Flourishing in Paul Tillich and Iris Murdoch, by Julia T. Meszaros. Oxford University Press, 2016. 227 pp. Kindle, $114.69. ISBN 978-0-19-876586-8.